Adrenomedullin for biologic‐resistant Crohn's disease: A randomized, double‐blind, placebo‐controlled phase 2a clinical trial. Issue 11 (25th July 2022) - Kita, Toshihiro; Ashizuka, Shinya; Takeda, Teruyuki; Matsumoto, Takayuki; Ohmiya, Naoki; Nakase, Hiroshi; Motoya, Satoshi; Ohi, Hidehisa; Mitsuyama, Keiichi; Hisamatsu, Tadakazu; Kanmura, Shuji; Kato, Naoya; et al.
Abstract: Background and Aim: Adrenomedullin is a bioactive peptide with many pleiotropic effects, including mucosal healing and immunomodulation. Adrenomedullin has shown beneficial effects in rodent models of inflammatory bowel disease and, more importantly, in clinical trials including patients with ulcerative colitis. We performed a successive clinical trial to investigate the efficacy and safety of adrenomedullin in patients with Crohn's disease (CD). Methods: This was a multicenter, double‐blind, placebo‐controlled phase 2a trial that evaluated 24 patients with biologic‐resistant CD in Japan. Patients were randomly assigned to three groups and were given an infusion of 10 or 15 ng/kg/min of adrenomedullin or placebo for 8 h per day for 7 days. The primary endpoint was the change in the CD activity index (CDAI) at 8 weeks. The main secondary endpoints included changes in CDAI from week 4 to week 24. Results: No differences in the primary or secondary endpoints were observed between the three groups by the 8th week. Changes in CDAI in the placebo group gradually decreased and disappeared at 24 weeks, but those in the adrenomedullin‐treated groups (10 or 15 ng/kg/min group) remained at steady levels for 24 weeks. Therefore, a significant difference was observed between the placebo and adrenomedullin‐treated groups at 24 weeks ( P = 0.043) in the mixed‐effects model. We noted mild adverse events caused by the vasodilatory effect of adrenomedullin. Conclusion: In this trial, we observed a long‐lasting (24 weeks) decrease in CDAI in the adrenomedullin‐treated groups. Adrenomedullin might be beneficial for biologic‐resistant CD, but further research is needed.